Nurses' attitudes, beliefs and practices on sexuality for cardiovascular care: A cross‐sectional study. Issue 5 (20th November 2018) - Wang, Panpan; Ai, Jiansai; Davidson, Patricia M.; Slater, Tammy; Du, Ruofei; Chen, Changying
Abstract: Aims and objectives: To describe nurses' attitudes, beliefs, and practices regarding sexuality care for patients with cardiovascular disease. Background: Limited sexual activity is common among patients with cardiovascular disease, yet assessment of sexuality and counselling is frequently not undertaken by nurses. Design: Cross‐sectional study. Methods: This study recruited 268 cardiac nurses from seven tertiary hospitals in five cities of Henan province. The Sexual Attitudes and Beliefs Survey, along with investigator‐developed questions regarding practices and perceived barriers, was administered to the nurses. The STROBE checklist was used to ensure quality reporting during this observational study (see Supporting Information Data S1 ). Results: The average age of nurses who participated was 31.81 years ( SD = 7.41). The average score of Sexual Attitudes and Beliefs Survey was 47.72 ( SD = 7.40), indicating moderate attitudinal barriers for nurses to discuss sexual activities with patients. Most nurses (91%) perceived that sexuality was too private to discuss with patients. Only 20% of nurses expressed that they would provide time to discuss sexual concerns with patients. Eighty per cent of nurses revealed that they felt uncomfortable discussing sexuality; moreover, they believed that hospitalised patients were too sick to be engaged in these types of conversations. Additionally, almost 85% of nurses conveyed that they have never conducted discussions regarding sexuality care in patients with cardiovascular disease. The most frequently reported perceived barriers preventing nurses from discussing sexual concerns included fear of offending patients (77.2%), uncertainty of how to communicate with patients (69.4%), feelings of embarrassment (67.5%), lack of safe and private environments (61.9%) and lack of knowledge (54.9%). Conclusion: Nurses in this cross‐sectional sample rarely discussed sexual concerns with their patients. There were several key barriers identified by nurses regarding providing sexuality care, including personal attitudes and beliefs, limited skills and knowledge, culture and organizational‐related barriers. Relevance to clinical practice: Targeted training for nurses and creating a culturally safe environment is recommended to improve management of sexuality in patients with CVD.